Body size and group size of Cuban tree frog (Osteopilus septentrionalis) tadpoles influence their escape behaviour - Bateman, Bill; Fleming, P. (Springer, 2015)
Tadpoles risk attack from both aquatic and aerial predators. We investigated how body size and group size influenced the behaviour of tadpoles before and during a predatory attack from above to test the predictions of the theoretical economic escape model. We examined escape (swimming) response of small and large Cuban tree frog (Osteopilus septentrionalis) tadpoles kept under three density treatments and predicted that increased group size, body size and depth in the water column would all reduce perceived risk and, therefore, escape responses to simulated predation. Compared with the lower density groups, tadpoles in higher density groups moved shorter distances, and many individuals did not even move away in response to being touched. Contrary to our predictions based on the economic escape model, smaller tadpoles (which should be more vulnerable to a greater suite of predators) were less reactive than larger tadpoles, and this result may reflect different costs of escape. Finally, although tadpoles might be exposed to a wider range of predator species (aerial as well as aquatic predators), we found no effect of initial depth on escape responses. In conclusion, it appears that the main benefit of increased group density in O. septentrionalis tadpoles is likely to be predator dilution, and that variation in densities of tadpoles influences the escape behaviour of individual tadpoles, regardless of tadpole size.